Screening of dementia indicating signs in adults with intellectual disabilities - Arvio Maria; Bjelogrlic-Laakso Nina (WILEY, 2022)
Background: In intellectual disability, the cognitive delay is observed during developmental age, whereas in dementia, cognitive decline occurs during post-developmental period. So far, the risk of dementia in people with intellectual disability, excluding those with Down syndrome, is poorly known.
Method: We screened dementia signs in a study group of 230 adults (34-80 years of age) with the help of the British Present Psychiatric State-Learning Disabilities assessment.
Results: Of the study members, 42% showed two or more signs. The overall frequency of symptoms did not differ between age groups. The number of individuals with a genetic syndrome or disease manifesting with a shortened lifespan was greater in the younger age groups when compared to the older age groups.
Conclusion: People with an intellectual disability represent numerous rare syndromes with comorbidities. It seems that dementia signs may affect any age groups of adults with intellectual disability.